Evaluation of the effects of microwave diathermy in patients with chronic low back pain - Shoma, FK; Habib, A; Mahmood, K; Muhammad, A; Hossain, MM; Siddique, N; Alam, MK (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13242 J. Dhaka Med. Coll. 2012; 21(1): 69-75